2019
DOI: 10.1002/da.22886
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the association between anxiety disorders and alcohol use disorder: A twin study

Abstract: Background: It is unknown whether social anxiety disorder (SAD) has a unique association with alcohol use disorder (AUD) over and beyond that of other anxiety disorders, how the associations develop over time, and whether the associations are likely to be causal.Methods: Diagnoses of AUD, SAD, generalized anxiety disorder, panic disorder, agoraphobia, and specific phobias were assessed twice using the Composite International Diagnostic Interview among 2,801 adult Norwegian twins. The data were analyzed using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Also in line with previous reports [4,8], the use of illegal substances, particularly cannabis, occurred more frequently among inpatients than outpatients, and among patients with schizophrenia and other psychoses compared to patients with other mental disorders. Although the association between the use of illicit drugs and severe mental illness is frequently recognized in the literature, the basis for the link is still being discussed [25][26][27]. For example, research concerning the association between schizophrenia and SUD has suggested a common genetic risk [28], or that patients with a genetic risk for schizophrenia are more vulnerable to substance use [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also in line with previous reports [4,8], the use of illegal substances, particularly cannabis, occurred more frequently among inpatients than outpatients, and among patients with schizophrenia and other psychoses compared to patients with other mental disorders. Although the association between the use of illicit drugs and severe mental illness is frequently recognized in the literature, the basis for the link is still being discussed [25][26][27]. For example, research concerning the association between schizophrenia and SUD has suggested a common genetic risk [28], or that patients with a genetic risk for schizophrenia are more vulnerable to substance use [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also in line with previous reports [7,10], use of illegal substances, particularly cannabis, occurred more frequently among in-patients than outpatients, and, as hypothesized, among patients with the most severe mental disorders (e.g., schizophrenia and other psychoses). Although the association between use of illicit drugs and severe mental illness is frequently recognized in the literature, the basis for the link is still being discussed [30][31][32]. For example, research concerning the association between schizophrenia and SUD has suggested a common genetic risk [33], or that patients with a genetic risk for schizophrenia are more vulnerable to substance use [34].…”
Section: Discussionmentioning
confidence: 99%
“…Also in line with previous reports [8,4], use of illegal substances, particularly cannabis, occurred more frequently among inpatients than outpatients, and among patients with the most severe mental disorders (e.g., schizophrenia and other psychoses). Although the association between use of illicit drugs and severe mental illness is frequently recognized in the literature, the basis for the link is still being discussed [25][26][27]. For example, research concerning the association between schizophrenia and SUD has suggested a common genetic risk [28], or that patients with a genetic risk for schizophrenia are more vulnerable to substance use [29].…”
Section: Discussionmentioning
confidence: 99%